2011
DOI: 10.1371/journal.pone.0026377
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of Near-Infrared Light Absorption Considering Individual Head and Prefrontal Cortex Anatomy: Implications for Optical Neuroimaging

Abstract: Functional near-infrared spectroscopy (fNIRS) is an established optical neuroimaging method for measuring functional hemodynamic responses to infer neural activation. However, the impact of individual anatomy on the sensitivity of fNIRS measuring hemodynamics within cortical gray matter is still unknown. By means of Monte Carlo simulations and structural MRI of 23 healthy subjects (mean age: years), we characterized the individual distribution of tissue-specific NIR-light absorption underneath 24 prefrontal f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
167
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 222 publications
(173 citation statements)
references
References 41 publications
6
167
0
Order By: Relevance
“…For a single source-detector arrangement, it was shown the light intensity is~10-20 times (depending on the model for estimating the hemodynamic signals and the SDS) more sensitive to the extracerebral compartment compared to the cerebral compartment (Al-Rawi et al, 2001;Liebert et al, 2004). The tissue-specific energy of light absorbed in the head by using a 3 cm SDS was investigated by Haeussinger et al (2011) by a Monte Carlo simulation based on three-dimensional segmented structural MRI data. They showed that the main part of the energy is absorbed by the extracerebral compartment (scalp:~76%), skull: 20%, CSF:~0.4%) compared to the cerebral one (gray matter:~3%, white matter:~0.0005%).…”
Section: Classification Of Signal Componentsmentioning
confidence: 99%
“…For a single source-detector arrangement, it was shown the light intensity is~10-20 times (depending on the model for estimating the hemodynamic signals and the SDS) more sensitive to the extracerebral compartment compared to the cerebral compartment (Al-Rawi et al, 2001;Liebert et al, 2004). The tissue-specific energy of light absorbed in the head by using a 3 cm SDS was investigated by Haeussinger et al (2011) by a Monte Carlo simulation based on three-dimensional segmented structural MRI data. They showed that the main part of the energy is absorbed by the extracerebral compartment (scalp:~76%), skull: 20%, CSF:~0.4%) compared to the cerebral one (gray matter:~3%, white matter:~0.0005%).…”
Section: Classification Of Signal Componentsmentioning
confidence: 99%
“…The hemodynamic signals in the EPM1 patients, who typically lack b-ERS, had a similar time course but were significantly lessened, possibly because of their mild cortical atrophy. Heinzel et al 2013 have recently reported that up to 41 % of the variance in the HHb signal and up to 18 % of the variance in the O 2 Hb signal in frontal regions can be explained by individual grey matter volume; moreover, differences in the distance between the scalp and cortex may affect the sensitivity of fNIRS (Haeussinger et al 2011). As in previous studies of EPM1 patients (Koskenkorva et al , 2012, we found that motor area CT was moderately reduced in our patients, and correlated with the reduction in the hemodynamic signals.…”
Section: Movement-related Eeg Changes and Hemodynamicsmentioning
confidence: 99%
“…Haeussinger et al [43] determined that the amount of radiation absorbed by the brain gray matter is in the order of 3% when a certain amount of radiation is applied to the scalp. Naeser and Hamblin advocated that red/near-infrared photons can penetrate deeply into the skull and reach the cortex.…”
Section: Tclt Radiation Transmission In the Skullmentioning
confidence: 99%